TI_GERICHTE 32.2013.133 vom 4. Juni 2013 , Negato il diritto ad una rendita. Confermata la perizia SAM e la valutazione SMR - TI Tribunale d'appello (2013)
Negato il diritto ad una rendita. Confermata la perizia SAM e la valutazione SMR